1.7 Times thermal expansion from glass to liquid. (1st January 2023) - Lu, Tong; Liu, Song Ling; Sun, Yong Hao; Liu, Zhao Yuan; Wang, Weihua; Pan, Mingxiang
Graphical abstract: Abstract: A novel experimental method for measuring the coefficient of thermal expansion of supercooled liquids is invented, as well as a new analytical methodology for determining the atomic-level thermal expansion of metallic glasses. We find a general rule of 1.7 times thermal expansion from glass to liquid for twenty bulk metallic glasses. This rule does not apply to other types of glasses or pure metals but only works for bulk metallic glasses containing copper or nickel. We revealed using molecular dynamics simulation that atomic shells of Cu (or Ni) with interatomic distances of 6.5–7.6 Å (or 6.4–7.6 Å for Ni) changed from 32 to 46 (or to 48 for Ni), when Cu 50 Zr 50 (or Ni 50 Zr 50 ) metallic glass enters its supercooled liquid, resulting in the sample's 1.7 times thermal expansion at the glass transition. This research provides insights on how bulk metallic glasses form and highlights the relevance of chemical order at an interatomic distance of 6.5–7.6 Å in driving glass transition.